PERSEPSI SESEORANG DALAM MEMILIH PEKERJAAN SEBAGAI DOSEN PERGURUAN TINGGI NEGERI DI INDONESIA - KEMAS M HUSNI THAMRIN; ABDUL BASHIR (Program Studi Magister Manajemen FE Unsri, 2015)
The purpose of this study was to determine the influence of financial factors and prestigious to be a career choice Lecturer State Universities in Indonesia. The sample in this study were 100 candidates for the civil service lecturers who do not yet have an academic level spread of Universities in Indonesia. Sampling was done at random (random sampling). The data used is primary data obtained from a questionnaire containing the answer options are arranged with ordinal scale. The analytical method used is descriptive analysis of qualitative and quantitative, further inferential analysis by estimating the multiple linear regression model based on statistical criteria test and test econometric criteria. Statistically, the results suggest that financial factors and prestigious affect positively and significantly to the preference factor, it is evidenced by a probability value of 0.000 is smaller than the critical value (alpha 0.05). Conclusion of the study is the financial factor and prestigious postiif and significant influence on the preference of a person chooses to become professors (educators) at Universities in Indonesia.